2021
DOI: 10.3389/fmed.2021.678185
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Signatures of Agitation Induced by Sevoflurane and Its Association With Genetic Polymorphisms

Abstract: Background: Volatile anesthetic-induced agitation, also called paradoxical excitation, is not uncommon during anesthesia induction. Clinically, patients with agitation may lead to self-injury or disrupt the operative position, increasing the incidence of perioperative adverse events. The study was designed to investigate clinical features of sevoflurane-induced agitation and examined whether any gene polymorphisms can potentially be used to predict agitation.Methods: One hundred seventy-six patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Moreover, a study has proven that sevoflurane disrupts folate metabolism and impedes neuronal transportation and communication, leading to demyelination of the juvenile brain 31 . A recent study by our research team also showed that MTRR gene polymorphisms may be associated with agitation susceptibility during sevoflurane anesthesia induction 20 . However, no study has yet reported the relationship between the MTRR gene and susceptibility to sevoflurane.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, a study has proven that sevoflurane disrupts folate metabolism and impedes neuronal transportation and communication, leading to demyelination of the juvenile brain 31 . A recent study by our research team also showed that MTRR gene polymorphisms may be associated with agitation susceptibility during sevoflurane anesthesia induction 20 . However, no study has yet reported the relationship between the MTRR gene and susceptibility to sevoflurane.…”
Section: Discussionmentioning
confidence: 95%
“…But lower Ai values are more likely to be associated with higher levels of sedation, even in individuals. Therefore, Ai can serve as a good guide for clinicians to titrate sevoflurane for the individuals 20,21 . Altogether, it must certainly be admitted that Ai is not the gold standard for sedation evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A biphasic reaction during induction of propofol anesthesia was also observed in spectral EEG analyses [ 41 , 42 ], i.e., a paradox excitation of EEG alpha and beta power even if unconsciousness was observed. Interestingly, nonlinear EEG methods do not follow a biphasic course but adequately reflect the hypnotic state [ 43 ].…”
Section: Discussionmentioning
confidence: 97%